2020
DOI: 10.2147/opth.s242804
|View full text |Cite
|
Sign up to set email alerts
|

<p>Emulsification of Different Viscosity Silicone Oil in Complicated Retinal Detachment Surgery: A Randomized Double-Blinded Clinical Trial</p>

Abstract: Objective: To study silicone oil (SO) emulsification, anatomic and visual outcome after complicated retinal detachment surgery by pars plana vitrectomy (PPV) with intraocular SO tamponade, comparing between low and high viscosity SO. Design: Randomized, double-blinded, controlled trial. Patients and Methods: Patients with complicated retinal detachment who had been surgically treated by PPV and intraocular SO tamponade were randomly divided into low viscosity (Group 1) or high viscosity (Group 2). Main Outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 16 publications
5
44
0
3
Order By: Relevance
“…The results of in vitro studies indicating that higher viscosity is associated with better long-term stability due to a lower rate of emulsification ( 1 , 4 , 27 ) have been contested in real-life. The only randomized, double-blinded, controlled study to date, conducted on patients with complicated retinal detachments, has shown that low viscosity SIO has a non-significant higher rate of emulsification on short and medium-term (up to 6 months) but much higher emulsification rate in endotamponades over this time as compared with higher viscosity SIO ( 28 ). Emulsification is not exclusively related to the physicochemical properties of SIO.…”
Section: Current State Of Knowledge Regarding Intraocular Pres- Sumentioning
confidence: 99%
See 1 more Smart Citation
“…The results of in vitro studies indicating that higher viscosity is associated with better long-term stability due to a lower rate of emulsification ( 1 , 4 , 27 ) have been contested in real-life. The only randomized, double-blinded, controlled study to date, conducted on patients with complicated retinal detachments, has shown that low viscosity SIO has a non-significant higher rate of emulsification on short and medium-term (up to 6 months) but much higher emulsification rate in endotamponades over this time as compared with higher viscosity SIO ( 28 ). Emulsification is not exclusively related to the physicochemical properties of SIO.…”
Section: Current State Of Knowledge Regarding Intraocular Pres- Sumentioning
confidence: 99%
“…While emulsification time is believed to largely vary between 5 and 24 months postoperatively ( 32 ), some reports emphasize that first signs of SIO emulsification appear in the first 3 months postoperatively ( 33 ) and even earlier, in the first month postoperatively ( 28 ). Since most of the cases have a certain degree of SIO emulsification within the first year postoperatively, there is a large consensus on the necessity to remove the SIO during this interval.…”
Section: Current State Of Knowledge Regarding Intraocular Pres- Sumentioning
confidence: 99%
“…L'émulsification, lorsqu'elle survient, apparaît généralement à partir de trois mois après le tamponnement [5], mais elle peut survenir plus précocement, surtout chez les enfants et les adultes jeunes.…”
Section: Discussionunclassified
“…The viscosity depends on the polymeric compound length and ranges from 1000 to 10000 centistokes (cs). Two types of highly purified polydimethylsiloxanes, low viscosity (1000 or 1300 cs) and high viscosity (5000 or 5700 cs), are commonly used in clinical practice [16]. In this study, 5700 cs SO (Oxane 5700; Bausch & Lomb, Germany) was injected in all patients.…”
Section: Methodsmentioning
confidence: 99%